Spatial Distribution of the Intellectual Capital of Russia - A. S. Mikhaylov; I. Yu. Peker (Высшее образование в России)
The study is focused on identifying the patterns of territorial distribution of intellectual capital in the Russian Federation. The purpose of this article is to assess the level of imbalance in the geographical distribution of the leading institutions of higher education in the context of the transition to the knowledge economy and to assess their integration into the regional innovation systems. The study is based on a quantitative analysis and qualitative assessment of the statistical data of the National Universities Ranking and the Project of the Russian Cluster Observatory. A grouping of universities into quartiles according to the cumulative total score obtained in the ranking is held, with the preparation of cartographic material. The intellectual capital of the regions is compared with the specialization of regional clusters. The results of the study confirm the significant accumulation of the intellectual capital in the two largest cities – Moscow and St. Petersburg, both in quantitative and qualitative terms. At the same time, the ranking includes universities of all large urban agglomerations. A number of regions actively involve universities in cooperation with industry, while many leave this area without proper attention. At the same time, the main resource for implementing the strategy of innovation development for regional authorities is state universities. The awareness of the authorities on the complementarity and involvement of knowledge-generating institutions and sectoral clusters makes it possible to understand the actual status of the regional innovation system and ensure the effective implementation of the principles of territorial-adaptive regional policy. This is the first empirical research in the context of Russia, in which data are used to assess the quality of national universities from the perspective of knowledge geography. Universities are considered as key sources for ensuring the intellectual capital of regional innovation systems, and the applied methodological approach enables evaluating their potential and involvement in cooperation with industry clusters.